Assessment Paddy Rice Ecosystem Services on Awareness and Satisfaction Level of Local People In Hongthai, Vietnam - Tran Thi, Nhung; Trinh Phuong, Ngoc; Phung Thanh, Thao (International Journal of Scientific Research and Management (IJSRM), 2023)
The paddy fields in Hongthai is considered as one of the most beautiful terraced fields in the Northeast of Vietnam. However, the efficiency of use of paddy rice ecosystem services here is still limited. The study was conducted to assess farmers’ awareness and satisfaction level of the paddy rice ecosystem services in Hongthai by using questionnaire survey. The results show that the paddy rice ecosystem provides many services to the farmers, specifically 12 non-market services, in which the majority of farmers clearly identify regulating services such as groundwater replenishment, flood prevention and soil erosion control. Also, although income from tourism is still low, most farmers in Hongthai are aware of the importance of cultural services such as tourist landscapes and culture. However, for other regulating and supporting services, farmers’ awareness is still limited. The satisfaction level of farmers in Hongthai with the paddy rice ecosystem services is still low (2.7/10). The reason is explained by the limited awareness of the ethnic people and the local government have not yet exploited and used the non-market ecosystem service values ​​to bring benefits. In the future, it is necessary to actively propagate and raise farmers' awareness about paddy rice ecosystem services and valuate non-market ecosystem services to provide a scientific basis for policy makers. The appropriate legal framework and supporting policies need to be developed for the conservation of paddy rice ecosystems through the services it provides.